A 10 year retrospective review on the management of upper airway obstruction in children with pierre robin sequence: the success of the nasopharyngeal airway. (24th May 2012) - Abel, F; Bajaj, Y; Wyatt, M; Wallis, C
Abstract : Introduction: Pierre Robin Sequence (PRS) is a congenital anomaly presenting with micrognathia, glossoptosis and a cleft palate. Although significant upper airway obstruction is common, especially during sleep, there isn't a general consensus about its management. In most centres, mandibular distraction surgery or insertion of tracheostomy is the recommended management for children with PRS not responding to conservative management such as positioning. The objective of this study was to present our experience with the use of nasopharyngeal airway in these patients as a possible alternative to surgery by retrospectively reviewing its use in our department over the last 10 years. Methods: This study was conducted jointly between the respiratory and otolaryngology departments. Only the children with all three characteristics of this condition have been included. The data collected included the method of airway management and oximetry data pre and post intervention. Results: Data was collected on 104 Pierre Robin patients referred to us from 2000 to 2010. Most of patients (64/104) were less than 4 weeks of age at referral. In this referred group, the airway symptoms were managed conservatively in 27 (25.9%), with nasopharyngeal airway (NPA) in 63 (60.6%) and tracheostomy in 14 (13.4%) patients. The duration of NPA use varied from 3 weeks to 27 months, the average being 7.9 months. There was an objective improvement on oximetry in all 63 patients with NPA. NPA did not improve symptoms subjectively or objectively in 14 patients who underwent a tracheostomy. There were no NPA related complications in this study. In this study 86.5% (90/104) PRS patients were successfully managed either conservatively or with the help of nasopharyngeal airway for few months. Conclusion: In majority of children (86.5%), the airway obstruction can be managed by conservative measures or nasopharyngeal airway for few months. A small number of children need to be managed with a tracheostomy. Although oximetry studies are not the most accurate tool to diagnose obstruction in itself, they were accurate enough to show objective improvement post insertion of NPA.